2023
DOI: 10.3389/fpls.2023.1137077
|View full text |Cite
|
Sign up to set email alerts
|

Resequencing of durian genomes reveals large genetic variations among different cultivars

Abstract: Durian (Durio zibethinus), which yields the fruit known as the “King of Fruits,” is an important economic crop in Southeast Asia. Several durian cultivars have been developed in this region. In this study, we resequenced the genomes of three popular durian cultivars in Thailand, including Kradumthong (KD), Monthong (MT), and Puangmanee (PM) to investigate genetic diversities of cultivated durians. KD, MT, and PM genome assemblies were 832.7, 762.6, and 821.6 Mb, and their annotations covered 95.7, 92.4, and 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…This research provides valuable insights into the molecular regulation of the key gene (MGL) responsible for the production of VSCs during the ripening process. Beyond investigations into molecular mechanisms during fruit post-harvest ripening, a few studies undertook a reanalysis of durian genomic data [115][116][117].…”
Section: Identification Of Ripening-related Tf Families During the Po...mentioning
confidence: 99%
See 1 more Smart Citation
“…This research provides valuable insights into the molecular regulation of the key gene (MGL) responsible for the production of VSCs during the ripening process. Beyond investigations into molecular mechanisms during fruit post-harvest ripening, a few studies undertook a reanalysis of durian genomic data [115][116][117].…”
Section: Identification Of Ripening-related Tf Families During the Po...mentioning
confidence: 99%
“…Without extensive genomic variation data spanning a diverse spectrum of durian varieties, including wild species, the identification of novel genes contributing to pivotal domestication traits on a global scale remains elusive. Noteworthy case studies in the existing literature have delved into genome resequencing in grapevine [122] and durian [117]. The latter study encompassed the whole-genome resequencing of three popular durian cultivars, unveiling genetic variations among them.…”
Section: Ripening-associated Biosynthetic Genes During the Post-harve...mentioning
confidence: 99%
“…Several scientific studies have suggested that deep sequencing can detect differential expression of genes, novel genes, transcripts, differentially expressed isoforms and splice variation unique for each condition (Jakhesara et al 2013). Transcriptome data of Malaysia and Thailand durian (Teh et al 2017;Husin et al 2022;Nawae et al 2023) and associated annotation data may fill in some gaps in durian molecular biology, often focused on phytochemical compositions and nutritional properties. The reference assembly of the durian genome (MK) used in this study consisted of chromosome-scale pseudomolecules with a length of 30 pseudomolecules larger than 10 Mb and comprising 95 % of the 712-Mb assembly (the pseudomolecules are hereafter referred to as chromosomes, numbered by scale).…”
Section: Introductionmentioning
confidence: 99%
“…The study reveals that a large portion of the Kradumthong (KD), Monthong (MT), and Puangmanee (PM) assemblies align closely with the Musang King (MK) assembly, surpassing 50 % identity. However, certain regions, particularly within repeat sections of the MK assembly, show lower identity percentages (Nawae et al 2023). Unknown transcripts (UTs) can include both coding and non-coding RNA sequences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation